Wnt1 and ?-Catenin Expression in Lobular Capillary Hemangioma: Immunohistochemical Study - Yuksel, Esma Inan; Balta, Hilal; Kocaman, Nevin (Galenos Publ House, 2023)
Introduction: Lobular capillary hemangioma (LCH) is a vascular neoplasia with a pathogenesis that has not been fully clarified. The Wnt signaling pathway plays an essential role in vasculogenesis and angiogenesis. The increased activity in the Wnt signaling pathway may cause some neoplastic proliferations. This study revealed the role of the Wnt1/beta-catenin signaling pathway in the development of LCH. Methods: The study included 30 LCH tissue samples. Vascular structures in healthy tissue surrounding LCH lesions were used as controls. Wnt1 and beta-catenin protein expressions in tumor tissue and surrounding tissue vascular structures were evaluated using the immunohistochemical method. Results: Wnt1 expression was 1.10 +/- 0.16 and 0.33 +/- 0.10 in the LCH and control groups, respectively, indicating a statistically significant difference (p<0.001). beta-catenin expression was 1.57 +/- 0.39 and 0.59 +/- 0.18 in the LCH and control groups, which was also statistically significant (p<0.001). Wnt1 and beta-catenin expressions were similar in the mucosal and cutaneous LCH lesions (p>0.05). Conclusion: In LCH, the Wnt1/beta-catenin signaling pathway expression is increased. This increase may be due to the increased Wnt1 gene expression, pathologies in different signaling pathways, or paracrine factors secreted from the tumor microenvironment. Treatment modalities targeting the Wnt1 signaling pathway may be promising for treating LCH.
Keywords: beta-catenin; hemangioma; immunohistochemistry; pyogenic granuloma; Wnt beta-catenin signaling pathway